Increased CSF levels of aromatic amino acids in hip fracture patients with delirium suggests higher monoaminergic activity. Issue 1 (December 2016) - Watne, Leiv; Idland, Ane-Victoria; Fekkes, Durk; Raeder, Johan; Frihagen, Frede; Ranhoff, Anette; Chaudhry, Farrukh; Engedal, Knut; Wyller, Torgeir; Hassel, Bjørnar
Abstract Background To examine whether delirium in hip fracture patients was associated with changes in the levels of amino acids and/or monoamine metabolites in cerebrospinal fluid (CSF) and serum. Methods In this prospective cohort study, 77 patients admitted with an acute hip fracture to Oslo University Hospital, Norway, were studied. The concentrations of amino acids in CSF and serum were determined by high performance liquid chromatography. The patients were assessed daily for delirium by the Confusion Assessment Method (pre-operatively and post-operative day 1–5 (all) or until discharge (delirious patients)). Pre-fracture dementia status was decided by an expert panel. Serum was collected pre-operatively and CSF immediately before spinal anesthesia. Results Fifty-three (71 %) hip fracture patients developed delirium. In hip fracture patients without dementia (n = 39), those with delirium had significantly higher CSF levels of tryptophan (40 % higher), tyrosine (60 % higher), phenylalanine (59 % higher) and the monoamine metabolite 5-hydroxyindoleacetate (23 % higher) compared to those without delirium. The same amino acids were also higher in CSF in delirious patients with dementia (n = 38). The correlations between serum and CSF amino acid levels were poor. Conclusion Higher CSF levels of monoamine precursors in hip fracture patients with delirium suggest a higher monoaminergic activity in the central nervous system during delirium in this patient group.